2019
DOI: 10.1111/jocd.12918
|View full text |Cite
|
Sign up to set email alerts
|

Penetration study of oils and its formulations into the human hair using confocal microscopy

Abstract: Summary Background Laser scanning confocal microscopy (LSCM) is a nondestructive method for observing the samples in three dimensions as well in their natural environment. Therefore, it is well suited for studying human hair. This investigation is focused on evaluating the comparative penetration ability of vegetable vs mineral oils and their formulations with excipient, in human hair. Aims Laser scanning confocal microscopy was employed to assess thin cross sections of human hair, treated with oils and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Shampoo is one of the most popular hair care products. 31 Nowadays, in addition to its primary function which is to wash the hair, shampoos are endowed with revitalising properties and beautify the hair. 32 Nearly 30.5% of women used natural oils and 45.3% associated natural oils with industrial oils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shampoo is one of the most popular hair care products. 31 Nowadays, in addition to its primary function which is to wash the hair, shampoos are endowed with revitalising properties and beautify the hair. 32 Nearly 30.5% of women used natural oils and 45.3% associated natural oils with industrial oils.…”
Section: Discussionmentioning
confidence: 99%
“…Shampoo was the product used by 75.3% of participants. Shampoo is one of the most popular hair care products 31 . Nowadays, in addition to its primary function which is to wash the hair, shampoos are endowed with revitalising properties and beautify the hair 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Srivastav et al have employed laser scanning confocal microscope observation using Nile Red as a dye to assess the penetration of oils into human hair 42) . It was observed that rice bran oil exhibited only 14% penetration, while light liquid paraffin oil exhibited 75% penetration.…”
Section: Visualization and Controlled Delivery Of Additivesmentioning
confidence: 99%
“…The results revealed that mineral oils had a better hair penetration ability than vegetable oils. Final formulations, containing oils and excipients, showed higher oil permeation ability, highlighting the influence that could be exerted by excipients [24].…”
Section: Microscopymentioning
confidence: 99%